(untitled) (Al-Academy, 2015)
Baghdad (the capital of the Abbasid Caliphate, and his legacy oldest civilizations in history, with glory ethyl). 1. benediction this city landmarks archaeological evidence of their own Kkabbab mosques and forms gates and (Aelchenachel) 2, which adorn the walls of buildings and Chaababeckha high and palm trees, all these vocabulary inspired artists embody Baghdad warmest dissolved in their artwork and all those who lived and grew up in Baghdad embodied in his memory for the nights Beauties and their lights and Hoa_khasha. Ceramic Arts art one who embodied the most important symbols that represent the beauty and credited with Baghdad. And many Iraqis potters inspired single Baghdadi in their work, notably ceramists late arrows Saudi which embodied single Baghdadi in most of its business .az found through access to business group varying time periods and analyze four samples that this actress has affected Bmorotha very civilized Laket we find most of its conception An authentic vocabulary Baghdadi symbolize the authenticity of the home and heritage of Baghdad. The vocabulary collected this way are almost tortured poetic beauty of fall for the receiver and the freshness and originality of Baghdad